Development of a Plasma-Based Assay to Measure the Susceptibility of Factor V to Inhibition by the C-Terminus of TFPIα - van Doorn, Peter; Rosing, Jan; Campello, Elena; Middeldorp, Saskia; Simioni, Paolo; Meijers, Joost C. M.; Hackeng, Tilman M.; Castoldi, Elisabetta (Thrombosis and Haemostasis, 2020)
Background Factor V (FV) is proteolytically activated to FVa, which assembles with FXa in the prothrombinase complex. The C-terminus of tissue factor pathway inhibitor-α (TFPIα) inhibits both the activation and the prothrombinase activity of FV(a), but the pathophysiological relevance of this anticoagulant mechanism is unknown. FV Leiden (FVL) is less susceptible to inhibition by TFPIα, while overexpression of FV splicing variants with increased affinity for TFPIα (FV-short) causes bleeding.Objective This study aims to develop a plasma-based assay that quantifies the susceptibility of FV(a) to inhibition by the TFPIα C-terminus.Materials and Methods FV in highly diluted plasma was preactivated with FXa in the absence or presence of the TFPIα C-terminal peptide. After adding prothrombin, thrombin formation was monitored continuously with a chromogenic substrate and prothrombinase rates were obtained from parabolic fits of the absorbance tracings. TFPI resistance was expressed as the ratio of the prothrombinase rates with and without peptide (TFPIr).Results The TFPIr (0.25–0.34 in 45 healthy volunteers) was independent of FV levels. The TFPIr increased from normal individuals (0.29, 95% confidence interval [CI] 0.28–0.31) to FVL heterozygotes (0.35, 95% CI 0.34–0.37) and homozygotes (0.39, 95% CI 0.37–0.40), confirming TFPI resistance of FVL. Two individuals overexpressing FV-shortAmsterdam had markedly lower TFPIr (0.16, 0.18) than a normal relative (0.29), in line with the high affinity of FV-short for TFPIα.Conclusion We have developed and validated an assay that measures the susceptibility of plasma FV to the TFPIα C-terminus. Once automated, this assay may be used to test whether the TFPIr correlates with thrombosis or bleeding risk in population studies.
Keywords: factor V; factor V Leiden; factor V-short; prothrombinase; tissue factor pathway inhibitor